In vitro anti-mycobacteria sensitivity and Kill-kinetics of allium ascalonicum L. (whole plant) on nontuberculous mycobacteria species (2014)
Allium ascalonicum L. (Shallot) was one of the herbs repeatedly identified from the result of our ethnobotanical survey for the treatment of tuberculosis and nontuberculous mycobacteria diseases. It has been reported to show inhibitory potentials against several pathogens. This plant is also known to form part of the diet of many people across the world. In the quest for a more active and body-friendly therapeutic agents, extracts of Allium ascalonicum (whole plant) were screened against four nontuberculous mycobacteria species namely, Mycobacterium fortuitum ATCC 684, Mycobacterium smegmatis ATCC 19420, Mycobacterium abscessus and Mycobacterium phlei ATCC 19240. In vitro susceptibilities testing was done using agar diffusion method with the concentrations of extracts ranging between 25 to 200 mg/mL. The minimum inhibitory concentration (MIC) was determined by agar dilution methods while the kill or bactericidal kinetics was measured by viable counting technique. Methanolic extract demonstated significant inhibitory potentials against three of the organisms at the test concentrations with a minimum inhibitory concentration (MIC) of 100 mg/mL, and 72-98 % kill of susceptible organisms in 24 hours. This significant activity may be due to the presence and right combination of the secondary metabolites in the plant such as alkaloids, flavonoids saponins, cardiac glycosides and essential oil, as revealed from our phytochemical screening. This study therefore confirms the scientific bases and justifies the use of Allium ascalonicum L. in traditional medicine practice in Nigeria and other parts of the world; and encourages its consumption as a natural prophylaxis against tuberculosis and nontuberculous mycobacteria diseases.